Discrimination and Skill Differences in an Equilibrium Search Model - Audra J. Bowlus; Zvi Eckstein (Tinbergen Institute, 1998)
In this paper we analyze an equilibrium search model with threesources for wage andunemployment differentials among workers with the same (observed)human capital but different appearance (race): unobservedproductivity (skill), search intensities and discrimination (Becker 1957)due to an appearance-based employer disutility factor. Because theyaffect the earnings distributionsdifferently, empirical identification of these potential sources forthe explanation of wage and unemployment differentials is possible.We show that the structural parameters of the model, including thefirm's disutility from certain workers, are identifiable usingstandard labor market survey data. Wedemonstrate identification using data from the National LongitudinalSurvey of Youth. Estimation of these parameters by matching momentsfrom a sample of black and white high school graduates implies:blacks have a 9% lower productivity level than whites;the disutility factor in employer's preferences is one-third of thewhite's productivity level; and50% of firms have a disutility factor in their utility toward blacks.
Keywords: 330; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Arbeitsproduktivität; USA